1995
DOI: 10.1002/mrd.1080400110
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of sulfated glycoprotein‐1 synthesis by nonciliated cells of the efferent ducts of adult rats

Abstract: The objective of this study was to define the factors regulating the endogenous production of sulfated glycoprotein-1 (SGP-1) in nonciliated cells of the efferent ducts. To this end we examined five different groups of animals undergoing the following experimental procedures: (1) hypophysectomized animals at 7, 14, and 28 days, (2) 7-day hypophysectomized rats receiving testosterone implants given at various time intervals thereafter, (3) castration at various time intervals up to 7 days, (4) 7-day castrated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In the efferent ducts, expression of SGP‐1 within lysosomes was not dependent on luminal or circulating androgens, nor was it dependent on a luminal factor entering the ducts from the testis (Rosenthal et al, 1995). However, the absence of SGP‐1 expression after hypophysectomy suggested that a pituitary factor, which may have a direct or indirect effect, is involved in its regulation in nonciliated cells of the efferent ducts (Rosenthal et al, 1995). Thus, different regulatory factors appear to come into play between the nonciliated cells of the efferent ducts and epithelial cells of the epididymis in the case of SGP‐1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the efferent ducts, expression of SGP‐1 within lysosomes was not dependent on luminal or circulating androgens, nor was it dependent on a luminal factor entering the ducts from the testis (Rosenthal et al, 1995). However, the absence of SGP‐1 expression after hypophysectomy suggested that a pituitary factor, which may have a direct or indirect effect, is involved in its regulation in nonciliated cells of the efferent ducts (Rosenthal et al, 1995). Thus, different regulatory factors appear to come into play between the nonciliated cells of the efferent ducts and epithelial cells of the epididymis in the case of SGP‐1.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study we noted that SGP‐1 expression in the efferent ducts was not dependent on luminal or circulating testicular factors, but was regulated by a pituitary factor (Rosenthal et al, 1995). Thus, it is of interest to determine whether this is also true for SGP‐1 expression in the different cell types and regions of the epididymis.…”
mentioning
confidence: 96%
“…In the reproductive system its expression appears to be induced by a pituitary factor (Rosenthal et al, 1995). Two mature forms of SGP-1 have been identified in Sertoli cells and in epithelial cells of the efferent ducts Igdoura et al, 1993): an intracellular form, which is also found in liver and spleen (O'Brien and Kishimoto, 1991).…”
Section: Introductionmentioning
confidence: 97%
“…The 70-kDa secretory prosaposin is a post-translationally modified form of the 65-kDa lysosomal prosaposin (27,28). This observation suggests that the Golgi apparatus must decode a sorting signal from the 65-kDa prosaposin to target it to the lysosomes before it is fully glycosylated in the distal compartment of this organelle.…”
mentioning
confidence: 99%